2015
DOI: 10.1007/s11661-015-2872-x
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Synchrotron X-ray Imaging Studies of the Ultrasound Shockwave and Enhanced Flow during Metal Solidification Processes

Abstract: The highly dynamic behaviour of ultrasonic bubble implosion in liquid metal, the multiphase liquid metal flow containing bubbles and particles, and the interaction between ultrasonic waves and semisolid phases during solidification of metal were studied in situ using the complementary ultrafast and high speed synchrotron X-ray imaging facilities housed respectively at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…It is not entirely clear how the fragmentation happens. Very limited direct observations show a mixture of rapid fragmentation from collapsing bubbles, slow separation of fragments assisted by pulsating bubbles and detachment of dendrites from the solidification front assisted by acoustic flow [14,15,16]. Most likely a combination of solute, flow and momentum effects plays role in the fragmentation.…”
Section: Main Mechanisms and Applications Of Ultrasonic Melt Processingmentioning
confidence: 99%
“…It is not entirely clear how the fragmentation happens. Very limited direct observations show a mixture of rapid fragmentation from collapsing bubbles, slow separation of fragments assisted by pulsating bubbles and detachment of dendrites from the solidification front assisted by acoustic flow [14,15,16]. Most likely a combination of solute, flow and momentum effects plays role in the fragmentation.…”
Section: Main Mechanisms and Applications Of Ultrasonic Melt Processingmentioning
confidence: 99%
“…One is the inoculation of nucleants via master alloys and through modifying the alloying chemistry . The other is the application of external fields by physical means . One of these is ultrasonic vibration or what will henceforth be called Ultrasonic Treatment (UST).…”
Section: Introductionmentioning
confidence: 99%
“…Both cavitation and acoustic streaming significantly affect grain refinement of the solidifying metal . Cavitation is the phenomenon of the formation, pulsation, growth, and implosion of cavities in the liquid phase and at liquid/solid/gas interfaces kinetically. In liquid metals, cavitation is difficult to model and to simulate on a large size scale due to the requirement to solve the coupled fluid flow and nonlinear cavitation equations in a very small time scale, for example, bubble dynamics time scale is in the range of 10 −20 –10 −8 s. Many efforts have been made to model and simulate cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [20] recently reported measurement of the size distribution of cavitation gas bubbles in an AlCu alloy melt using the synchrotron X-ray radiography whilst the current authors used it to study the ultrasonic capillary effect in a molten metallic alloy [21]. Tan et al [22] observed shockwaves and flows upon cavitation in Bi-based alloys. However, the growth behaviour, number density and underlying mechanisms of cavitation bubble have not been investigated.…”
Section: Introductionmentioning
confidence: 99%